2005
DOI: 10.1007/s11064-005-6529-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mild and Severe Hypoxia on Rat Cortical Synaptosomes

Abstract: Brain ischemia results in neuronal injury and neurological disability. The present study examined the effect of mild (6% O2) and severe (2% O2) hypoxia on mitochondria of rat cortical synaptosomes. During mild and severe hypoxia, JO2 and ATP production significantly decreased and mitochondrial membranes depolarized. Synaptosomal calcium concentration increased slightly, albeit not significantly. After a 1 h re-oxygenation period, JO2, ATP production and mitochondrial membrane potential returned to control leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Thus, isoprostanes, which are more chemically and metabolically stable, are good in vivo biomarkers of oxidative damage [36]. Accordingly we demonstrated that synaptosomes, which are pinched off resealed isolated nerve terminals prepared from cortical brain neurons containing essentially mitochondria, enzymes and vesicles of neurotransmitters, are very susceptible to oxidants and to hypoxia [38,39].…”
Section: Discussionmentioning
confidence: 82%
“…Thus, isoprostanes, which are more chemically and metabolically stable, are good in vivo biomarkers of oxidative damage [36]. Accordingly we demonstrated that synaptosomes, which are pinched off resealed isolated nerve terminals prepared from cortical brain neurons containing essentially mitochondria, enzymes and vesicles of neurotransmitters, are very susceptible to oxidants and to hypoxia [38,39].…”
Section: Discussionmentioning
confidence: 82%
“…Synaptosomes are nerve terminals prepared from gently homogenized brain, which reseal after separation from the nerve fibres; they possess many of the properties of the synapses. We used cortical synaptosomes because mitochondria from different tissues have different susceptibility to physical stress and neuronal mitochondria are more vulnerable to oxidants than astrocytic mitochondria [Aldinucci et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…The release of free iron and the production of protein carbonyls, 4 hydroxynonenal (4HNE) protein adducts and F 2 -isoprostanes after hypoxia are closely correlated, as demonstrated by our previous paper [11], and are all highly accurate quantitative markers of oxidative stress [12]. Moreover, we have demonstrated that synaptosomes (pinched off and resealed isolated nerve terminals prepared from cortical brain neurons and essentially containing mitochondria, enzymes and vesicles of neurotransmitters) are very susceptible to oxidants and to hypoxia [13,14].…”
Section: Introductionmentioning
confidence: 83%